Language Use and Discoursal Strategies in Peer Religious Mentoring - Phyllis Ghim Lian Chew (Journal of English Language Teaching and Linguistics, 2016)
This paper focuses on language use and discoursal strategies in an Islamic boys camp and draws from theoretical frameworks such as the ethnography of speaking, conversation analysis and discourse analysis as a means to examine the phenomena of religious mentoring and socialization.   The article found that mentees were socialized through senior peers’ linguistic strategies such as language choice and code-switching and discoursal strategies such as humor, mock-demonstrations  – all of which played a major role in building solidarity, group support and brotherly bonding.